Penerapan Doktrin Fiduciary duty dalam Hukum Korporasi Indonesia: Studi Kasus Direktur Utama PT Timah Tbk pada Putusan Nomor 80/Pid.Sus-Tpk/2024/Pn.Jkt.Pst (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study discusses the application of the fiduciary duty doctrine in Indonesian corporate law and its relationship to the legal liability of the President Director in Decision Number 80/Pid.Sus-TPK/2024/PN.Jkt.Pst in the case of PT Timah Tbk. This study uses a normative juridicial method with a statutory regulatory approach and a case approach, namely by examining law Number 40 of 2007 concerning Limited Liability Companies and relevant court decisions. The results of the study indicate that fiduciary duty is a basic obligation that must be carried out by directors in managing the company, which includes good faith, prudence, and loyalty to the interest of the company. However, in the case of PT Timah Tbk, the former President Direktor was proven not to have carried out these obligations properly. This is seen from the abuse of office, involvement in illegal mining practices, and the formation of shell companies that ultimately resulted in state losses. Violations of these principles not only have an impact on civil aspects, but also have criminal consequences. Therefore, strengthening the principles of fiduciary duty and Good Corporate Governance is very necessary to increase the accountability of directors.